Factors Affecting Performance Employees: Motivation, Leadership, Environment Work, Organizational Culture, and Achievement Work - Muzaki, Feri Ihsan; Ulfa Sari, Wita; Kharisma Putri, Indah; Septian Arianto, Risky; Putra, Riyan Sisiawan (Universitas Nahdlatul Ulama Sidoarjo, 2023)
This study aims to determine: (1) The effect of motivation on employee performance; (2) The influence of leadership on employee performance; (3) The influence of the work environment on employee performance; (4) The influence of organizational culture on employee performance; (5) The effect of work performance on employee performance. The method used, namely Literature review, provides a framework related to new findings and previous findings in identifying indications of whether or not there is progress from the results of a particular study. The method used in the literature review is through a systematic approach to analyzing data in a simplified approach. The author takes all the research designs used in identifying the influence of work motivation, leadership, environment, organizational culture, and work performance on employee performance.